Dorsal, a Drosophila Rel-like protein, is phosphorylated upon activation of the transmembrane protein Toll. - Gillespie, S K (1994)
The nuclear import of dorsal, a Drosophila Rel homolog, is directed by a spatially restricted extracellular ligand in blastoderm embryos. We have demonstrated both that dorsal is an embryonic phosphoprotein and that its phosphorylation state is regulated by an intracellular signaling pathway initiated by the transmembrane receptor Toll. Immunoblot analysis of cytoplasm from precisely staged embryos revealed that the phosphorylation state of dorsal is altered during the time period that Toll is activated. Moreover, mutations that constitutively activate Toll stimulated dorsal phosphorylation, while mutations that block Toll activation reduced the level of dorsal phosphorylation. We further demonstrated that signal-dependent dorsal phosphorylation is modulated by three intracellular proteins, pelle, tube, and cactus. Using double-mutant embryos, we then explored the nature of the kinase activity responsible for dorsal phosphorylation. We found that free dorsal is a substrate for a signal-independent kinase activity. In addition, our results imply that dorsal is a substrate for a Toll-dependent kinase. These results are consistent with the hypothesis that phosphorylation of Rel-related proteins may be required for the proper nuclear localization and transcriptional activity of these proteins.